Neglected posterior dislocation of the shoulder: A systematic literature review - Wu Xu; Li-Xin Huang; Jiong Jiong Guo; Ding-Hua Jiang; Yong Zhang; Hui-Lin Yang (Journal of Orthopaedic Translation, 2015)
Posterior dislocation of the shoulder (PSD) is a rare injury; the diagnosis is often missed on initial examination. We present a systematic review of the current literature and discuss the key of the diagnosis of PSD. We searched the MEDLINE, PubMed, EMBASE, MD Consult, and the Cochrane Controlled Trial Register databases for the articles according to our eligibility criteria. Finally, 53 articles were included in our systematic review. There were 242 shoulders in 205 patients. In total, in the initial assessment with anteroposterior radiographs in 166 cases, only 19 (11.4%) cases confirmed the right diagnosis. When anteroposterior combined with axillary or Y view radiographs or computed tomography were present as the initial assessments in 36 cases, the diagnoses were made correctly and timely (100%). When axillary or Y view radiographs or computed tomography were taken subsequently, the diagnosis was confirmed in all 205 patients.